Continental flood basalts derived from the hydrous mantle transition zone - Wang, Xuan-Ce; Wilde, Simon; Li, Q.; Yang, Y. (Nature Publishing Group, 2015)
It has previously been postulated that the Earth's hydrous mantle transition zone may play a key role in intraplate magmatism, but no confirmatory evidence has been reported. Here we demonstrate that hydrothermally altered subducted oceanic crust was involved in generating the late Cenozoic Chifeng continental flood basalts of East Asia. This study combines oxygen isotopes with conventional geochemistry to provide evidence for an origin in the hydrous mantle transition zone. These observations lead us to propose an alternative thermochemical model, whereby slab-triggered wet upwelling produces large volumes of melt that may rise from the hydrous mantle transition zone. This model explains the lack of pre-magmatic lithospheric extension or a hotspot track and also the arc-like signatures observed in some large-scale intracontinental magmas. Deep-Earth water cycling, linked to cold subduction, slab stagnation, wet mantle upwelling and assembly/breakup of supercontinents, can potentially account for the chemical diversity of many continental flood basalts.